MODELOS FÍSICOS EM ESCALA COMO FERRAMENTA DE PROJETO PARA DIMENSIONAMENTO DE SISTEMAS DE DUTOS DE LUZ - Silveira, Ana Paula; Luz, Bruna; Monteiro, Leonardo (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Not only is daylight in architecture an aesthetic issue, concerning economic, social and environmental aspects as well. The exploitation of its benefits can be enlarged by the adoption of non-conventional systems, making it possible for light to reach areas with no contact with the direct source, such as underground spaces. This paper presents a design process proposal for light pipes systems relating mathematical dimensioning models and the use of scaled physical models. The former obtains the required number of pipes while the latter is used as a tool for the qualitative analysis of the many possible arrangements. A case study is presented as a demonstration of the benefits, drawbacks and restrictions this designing process faces.